Adsorptive removal of phenol from aqueous solution on a modified palm shell-based carbon: fixed-bed adsorption studies - Garba, A. (Taylor and Francis Inc., 2016)
In this study, activated carbon from oil palm shell was produced by two-step chemical activation using K2CO3 as the chemical activant in the ratio 1:2 for the removal of phenol in a fixed-bed column. The characterization of the carbon was carried by Fourier Transform Infrared spectroscopy, Scanning electron microscope, thermogravimetric analysis, zeta potential, Brunauer–Emmett–Teller (BET) surface area, Elemental and Proximate analysis. The Langmuir surface area, BET surface area, and pore volume of the carbon were 817 m2/g, 707 m2/g, and 0.31 cm3/g, respectively. The examination of several factors including bed depth, initial phenol concentration, and flow rate were carried out at constant pH of 6.5. The maximum sorption capacity of the carbon for phenol was 238.12 at 250 mg/L initial phenol concentration, 1 cm bed depth, and 9 mL/min flow rate. Thermodynamic parameters were determined to analyze the behavior of phenol uptake at different temperatures. Breakthrough curve models indicated that Yoon–Nelson model fitted the experimental data better than Adams–Bohart and Thomas models. According to the results obtained, activated carbon prepared from oil palm shell, modified with ammonia solution was an effective, sustainable, low cost, and alternative adsorbent for the removal of phenol in aqueous solutions.